Academic Language Register In Arabic Articles From Al-Majallah Al-Urduniyyah Fi Al-Ulum Al-Tarbawiyyah - Norhayuza Mohamad; Mohamad Nor Amin Samsun Baharun; Zuraini Mohd Ramli; Ahmad Wan Abd Rahman; Ahmad Basyar Saifuzzaman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This study falls under discourse analysis studies, focusing on using the academic register in Arabic research articles. Language register refers to using a form of language in a specific context. The use of language register varies according to the structure of discourse and field. For example, language register is used in scientific discourse, entertainment, politics, and health. Using accurate and appropriate scientific language in terms of vocabulary can demonstrate the strength of an article in reporting research results. The current study was conducted to identify the use of the academic register in Arabic via research articles focusing on academic vocabulary. This study was prompted by several issues, such as the weakness of students and researchers in producing quality research reports from the aspect of scientific writing, in addition to the limited number of studies about the academic language register in Arabic. This study was descriptive, using a qualitative approach and content analysis techniques. The unit analyzed was academic vocabulary words taken from six journal articles on Arabic language issues. All articles were written by native Arabic speakers and published by the Arabic journal “al-Majallah al-Urduniyyah fi al-Ulum al-Tarbawiyyah” in Jordan. The academic language register was analyzed using the approach of Ure and Ellis (1977). It was based on the 100 academic vocabulary words (Academic Vocabulary List or AVL) generated by Gardner and Davies (2014). The study's results found that all the suggested words from the AVL were used by Arabic-language researchers in writing their articles with various frequencies. Out of the 100 words selected from the AVL, 71 to 90 vocabulary words were used in each article. The most used word was the word دِرَاسَة which appeared 464 times, but the word شَجَّعَ appeared only 3 times, the lowest frequency.